Efektivitas Program Restrukturisasi Dalam Mengatasi Pembiayaan Bermasalah Atas Dampak Pandemi Covid-19 Di Bank Syariah Indonesia Cabang Bandar Lampung - Fauzi Hasyim (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2023)
The Organization for Economic Co-Operation and Development (OECD) stated that the covid-19 pandemic had implications for various aspects. Indonesia, which is dominated by the existence of UMKM as the backbone of the national economy, is also seriously affected not only in terms of total production and trade value but also the number of workers who have lost their jobs. This has an impact on the supply side, namely termination of employment and the threat of non-performing bank credit payments. Based on this, the effectiveness of the restructuring program in overcoming non-performing financing becomes interesting to study. This type of research is descriptive with a qualitative approach. The results showed that the researchers saw that the level of compliance with financing installment payments after the restructuring of financing had increased. So it can be concluded that the restructuring program is effective in overcoming problem financing in banks. The researcher's suggestion need for socialization related to POJK Number 11/PJOK.03/2020 concerning the national economic stimulus as a countercyclical policy due to the impact of the spread of COVID-19.